The Ugly duckling - Andersen, H. C. (Hans Christian), 1805-1875. (Harlow, Essex : Longman, 1987)
An ugly duckling spends an unhappy year ostracized by the other animals before he grows into a beautiful swan.
K-3.
K-3
Keywords: Fairy tales; Fairy tales